Sacubitril–valsartan versus enalapril for the treatment of acute decompensated heart failure in Chinese settings: A cost-effectiveness analysis - Hu, Tianyang; Liu, Yiting; Lou, Yake (Frontiers in Pharmacology, 2023)
Background: The episode of acute decompensated heart failure (ADHF) is the main cause of hospitalization for heart failure (HF). Sacubitril–valsartan has been proven to be effective in reducing the risks of hospitalization for HF in ADHF. When to initiate sacubitril–valsartan in ADHF to make it the most cost-effective in China remains unclear. Methods: A lifetime Markov model with a 1-month cycle length was developed to evaluate the cost-effectiveness of early or late initiation of sacubitril–valsartan versus enalapril in ADHF. Early initiation of sacubitril–valsartan meant that it was initiated after stabilization from ADHF, and late initiation of sacubitril–valsartan meant that it was initiated after stabilization from HF, which includes no hospitalization for at least three consecutive months. The primary outcome was the incremental cost-effectiveness ratio (ICER), expressed as the ratio of incremental cost to incremental effectiveness. The secondary outcomes were total costs and total effectiveness. Three times of per capita GDP of China in 2021 was set as the willingness-to-pay threshold. One-way sensitivity analysis and probabilistic sensitivity analysis were employed to test the robustness of the results. Results: The early initiation of sacubitril–valsartan treatment resulted in an ICER of 3,662.4 USD per quality-adjusted life year, lower than the willingness-to-pay threshold, and the late initiation of sacubitril–valsartan treatment gained an ICER of 4,444.4 USD/QALY, still lower than the willingness-to-pay threshold. One-way sensitivity analysis showed that our results were robust, and probabilistic sensitivity analysis suggested that early initiation of sacubitril–valsartan in ADHF was cost-effective under a 97.4% circumstance. Conclusion: Early initiation of sacubitril–valsartan after stabilization of ADHF is highly cost-effective compared with the use of enalapril; late initiation of sacubitril–valsartan after stabilization of HF is still cost-effective but not as cost-effective as early initiation of sacubitril–valsartan in ADHF. For Chinese ADHF patients, the time to initiate sacubitril–valsartan should be when the patient is stabilized from ADHF rather than when stabilized from HF, from the perspective of economic evaluation.